2020
DOI: 10.1177/1758573220922845
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the minimum two-year follow-up standard after total shoulder arthroplasty—Is one year sufficient?

Abstract: Background US Food and Drug Administration Investigation Device Exemption studies and academic journals emphasize the importance of two-year follow-up data in reporting outcomes of total shoulder arthroplasty, but there is limited data evaluating appropriate follow-up length. We aim to evaluate change in postoperative outcomes and complications between one and two years following anatomic and reverse total shoulder arthroplasties. Methods We retrospectively identified 250 patients who underwent anatomic and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, Mahendraraj et al 8 report in their retrospective review of 250 shoulder arthroplasty patients in a single-surgeon arthroplasty registry that there were no additional complications or evidence of implant failure identified between years one and two postoperatively. In addition, they state that the American Shoulder and Elbow Score (ASES) and Visual Analogue Scale (VAS) PROMs did not increase.…”
Section: Resultsmentioning
confidence: 99%
“…However, Mahendraraj et al 8 report in their retrospective review of 250 shoulder arthroplasty patients in a single-surgeon arthroplasty registry that there were no additional complications or evidence of implant failure identified between years one and two postoperatively. In addition, they state that the American Shoulder and Elbow Score (ASES) and Visual Analogue Scale (VAS) PROMs did not increase.…”
Section: Resultsmentioning
confidence: 99%
“…The two-year follow-up requirement is most likely based from studies on hip and knee arthroplasty, which indicate patients continue to recover two years after surgery [ 52 ], rather than research on shoulder arthroplasty recovery [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…An appropriate alternative could be to use a lower number of surgeries, such as 150 surgeries at two-year follow-up for clinical outcomes, in addition to PROMS data for 100 patients at one-year follow-up. A study demonstrated that shoulder arthroplasty investigations may not require the minimum two-year clinical follow-up, as PROs and range of motion scores plateaued at one year postoperatively without further complications [ 53 ]. For benchmarking purposes, further research is required to determine the appropriate number of surgeries for safety and clinical outcomes for the various indications for shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many research publications require a minimum of 1 or 2 years of postoperative follow-up. 1,8,25,32 Although this standard allows for adequate understanding of recovery, results may be biased because healthy patients are less likely to continue medical assessment after substantial improvement. 19 Remote collection of PROs could support this or even longer follow-up.…”
Section: Discussionmentioning
confidence: 99%